Hubungan Faktor Individu dan Lingkungan dengan Perilaku Menyalahgunakan Napza di Lembaga Pemasyarakatan Kelas II.a Pekanbaru - Usraleli Usraleli; Novy Helena; Basmanelly Basmanelly (Universitas Batanghari Jambi, 2020)
In 2015 the NAPZA case in Riau expected to increase sharply compared to 2014 due to its geographical location that surrounded by the ocean that it had a beach which was easy for a place for drug traffic. Individual factors that cause drug abuse were curiosity, desires to be accepted by the group, following tendencies, seeking pleasure, seeking attention and imitating famous people. Whereas environmental factors were from family relations who were not harmonious, poor interpersonal relationships, parents/family members were also drug users, the communities are less concerned, lack social control and group pressure. The purpose of this study is to identify the relationship between individual factors and the environment with drug abuse in class II A prisons in Pekanbaru. This research was conducted from March to August 2015 with a cross-sectional analytic design on 89 assisted residents. The results showed that all individual and environmental factors had a relationship with drug abuse behaviour except for the environmental sub-variables, namely parents/family members as well as users. The contribution of Individual factors in drug abuse indicated that of the six most prominent individual factors are the average curiosity of the inmates is 75.78 ± 15.987 (the lowest results are 25, and the highest is 100. The least was the common desire to seek attention in abusing NAPZA is 52.83 ± 18.018 (the lowest results are 8, and the highest is 100. The results of this study could use as material for coaching activities related to individual and environmental factors in prison.